2013
DOI: 10.1002/pon.3300
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms after treatment in hepatocellular carcinoma survivors: prevalence, determinants, and impact on health‐related quality of life

Abstract: This study suggests that after treatment, many HCC survivors experience depressive symptoms that are strongly associated with poorer HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…A poorer global QoL at baseline was also found to be a moderator of the effect of the NUCAI in both the full-case and intention-to-treat analyses, with patients with a worse global QoL at baseline responding better (a decrease of 6.7 points on the depressive symptoms scale) to treatment than patients with a better global QoL. While we did not find any articles in the literature that expressly investigated this, several studies have shown that higher depressive symptom scores or depression are related to a lower global QoL in cancer patients [ 19 , 25 , 26 ]. Overall, no significant improvements were found for patients who had high (+1 SD) global QoL, emotional functioning, and social functioning scores.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A poorer global QoL at baseline was also found to be a moderator of the effect of the NUCAI in both the full-case and intention-to-treat analyses, with patients with a worse global QoL at baseline responding better (a decrease of 6.7 points on the depressive symptoms scale) to treatment than patients with a better global QoL. While we did not find any articles in the literature that expressly investigated this, several studies have shown that higher depressive symptom scores or depression are related to a lower global QoL in cancer patients [ 19 , 25 , 26 ]. Overall, no significant improvements were found for patients who had high (+1 SD) global QoL, emotional functioning, and social functioning scores.…”
Section: Discussionmentioning
confidence: 74%
“…It should be mentioned that, with the NUCAI, patients are encouraged to bring their partners to intervention sessions. Mikoshiba et al [ 19 ] found that living alone was associated with an increased likelihood of depressive symptoms in patients with liver cancer. Perhaps if a partner follows the intervention with the patient, he/she can discuss the intervention with the patient at home and might stimulate and support the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They report lower QOL than the general population and than those with liver disease but without HCC [15, 16]. Poor QOL is driven by several symptoms including fatigue, weakness, anorexia, abdominal pain/bloating, and depression [14, 1619]. …”
Section: Introductionmentioning
confidence: 99%
“…Depression has a substantial effect on work and daily lives, sleeping, and general health [ 16 , 17 ]. Studies in HCC patients treated with TACE revealed that patients experienced variant depressive episodes during posttreatment [ 5 , 7 , 18 , 19 ] and there was a strong correlation with fatigue [ 18 ] and sleep disturbance [ 5 , 18 ], impacting quality of life [ 19 ].…”
Section: Introductionmentioning
confidence: 99%